NEUROMUSCULAR BLOCKADE REVERSAL AND TRACHEAL INTUBATION DURING RECONSTRUCTIVE OPERATIONS ON THE CAROTID ARTERIES - A. Yu. Novikov; I. E. Golub; L. V. Sorokina; A. V. Lugovoy (Вестник анестезиологии и реаниматологии)
The paper presents the results of using sugammadex and an antireflux endotracheal tube during surgical treatment for stenotic lesions of the extracranial internal carotid artery. It shows the results of examining a group of patients with carotid atherosclerotic lesion at high surgical/anesthetic risk in whom the anesthetic regimen used neuromuscular blockade reversal and an antireflux endotracheal tube. The paper emphasizes the importance of the proposed procedure that may positively affect the entire early postoperative period, restores muscle tone rapidly and adequately, statistically significantly shows a 1.4-fold reduction in the time of awakening, tracheal extubation and activation, and leads to hemodynamic stabilization.